2011
DOI: 10.1161/circimaging.110.958777
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Detection of the Vulnerable Plaque

Abstract: C oronary heart disease (CHD) remains the leading cause of death in the United States, and an estimated 1.4 million Americans have a heart attack each year. Over the past 2 decades, the concept of the "vulnerable plaque" (VP) being responsible for the majority of acute coronary syndromes (ACS) has become widely accepted. Coincidentally, there has been rapid expansion of coronary imaging modalities, both invasive and noninvasive, seeking the ability to detect high-risk plaques before their disruption and format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 68 publications
0
41
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] With regard to atherosclerotic plaques, IVOCT has demonstrated an ability to differentiate lipid, calcium, and fibrous tissue 13,14 and to quantify microscopic features such as macrophage content. 9 We have previously reported on IVOCT image analysis relating to segmentation, quantification, and visualization of plaques, stents, and other vessel wall components.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] With regard to atherosclerotic plaques, IVOCT has demonstrated an ability to differentiate lipid, calcium, and fibrous tissue 13,14 and to quantify microscopic features such as macrophage content. 9 We have previously reported on IVOCT image analysis relating to segmentation, quantification, and visualization of plaques, stents, and other vessel wall components.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated OCT imaging of the ablated volume which provided high contrast images of the gas bubble resulting from ablation. The use of OCT in conjunction with plaque ablation is convenient because IV-OCT devices already provide clinicians a high-resolution tool for plaque recognition and characterization 15 . The results showed that pulse energies below 4 J provided axially isolated ablation volumes, such that ablation targeted deeper than 20 m rarely caused surface damage.…”
Section: Discussionmentioning
confidence: 99%
“…NIRS can provide a semiquantitative measure of lipid burden (so-called lipid-core burden index). NIRS is Food and Drug Administration approved for the detection of lipid-core plaques, and it is under active investigation for the detection of vulnerable plaques 11 and plaques at risk of periprocedural myocardial infarction. 12 To date, however, limited information on NIRS' ability to detect neoatherosclerosis is available.…”
Section: See Article By Madder Et Almentioning
confidence: 99%